Fabrication of ZnO-SiO2 Nanocomposite Materials Prepared by a Spray Pyrolysis for the Photocatalytic Activity under UV and Sunlight Irradiations. Issue 1 (April 2020) - Kusdianto, K; Widiyastuti, W; Shimada, M; Qomariyah, L; Winardi, S
Abstract: ZnO is the most widely used for photocatalytic application among various semiconductor materials. The photocatalytic performance of ZnO can be enhanced by doping with other materials. In this study, ZnO-SiO2 nanocomposites have been successfully fabricated by gas-phase method via spray pyrolysis. The effect of temperature of spray tubular furnace reactor ranging from 300 to 600 °C on the photocatalytic activity of ZnO-SiO2 nanocomposites were investigated. Colloidal SiO2 with concentration at 1 %wt was used as dopant to ZnO particles. The pristine ZnO was also synthesized at temperature of 400 °C for comparable. Zinc acetate and water glass were used as the precursors for fabrication ZnO-SiO2 nanocomposites. At first, the water glass was synthesized by sol-gel method to produce colloidal SiO2 nanoparticles and then mixed with zinc acetate before subjecting to the spray reactor. The produced nanocomposite materials were collected by an electrostatic precipitator. Scanning electron microscopy and energy-dispersive X-ray (SEM-EDX), X-ray diffraction (XRD), and Fourier-transform infrared (FTIR) were used for characterization the products. While UV-Vis spectrometry was used to measure the concentration of methylene blue (MB) before and after irradiations. SEM images indicated that the morphology of particles was as sphere-like structures with interwoven nanoplate and the agglomeration of particles can be suppressed by adding SiO2 . The average particle size of the produced nanocomposite decreased with increasing synthesis temperature. XRD analysis also confirmed that the crystallite size increased with increasing temperature. Finally, the photocatalytic activity of the ZnO-SiO2 nanocomposites were calculated by evaluating the methylene blue degradation aqueous solution under UV and sunlight irradiations. MB degradation efficiency under UV light was much lower than that of under sunlight irradiation. It also showed that the best photocatalytic performance reached 96 % when the synthesis temperature was set as high as 400 °C with SiO2 concentration at 1 %wt under sunlight irradiation.